The secreted esterase of propionibacterium freudenreichii has a major role in cheese lipolysis - Abeijon Mukdsi, Maria Claudia (2014)
Free fatty acids are important flavor compounds in cheese. Propionibacterium freudenreichii is the main agent of their release through lipolysis in Swiss cheese. Our aim was to identify the esterase(s) involved in lipolysis by P. freudenreichii. We targeted two previously identified esterases: one secreted esterase, PF#279, and one putative cell wall-anchored esterase, PF#774. To evaluate their role in lipolysis, we constructed overexpression and knockout mutants of P. freudenreichii CIRM-BIA1T for each corresponding gene. The sequences of both genes were also compared in 21 wild-type strains. All strains were assessed for their lipolytic activity on milk fat. The lipolytic activity observed matched data previously reported in cheese, thus validating the relevance of the method used. The mutants overexpressing PF#279 or PF#774 released four times more fatty acids than the wild-type strain, demonstrating that both enzymes are lipolytic esterases. However, inactivation of the pf279 gene induced a 75% reduction in the lipolytic activity compared to that of the wild-type strain, whereas inactivation of the pf774 gene did not modify the phenotype. Two of the 21 wild-type strains tested did not display any detectable lipolytic activity. Interestingly, these two strains exhibited the same single-nucleotide deletion at the beginning of the pf279 gene sequence, leading to a premature stop codon, whereas they harbored a pf774 gene highly similar to that of the other strains. Taken together, these results clearly demonstrate that PF#279 is the main lipolytic esterase in P. freudenreichii and a key agent of Swiss cheese lipolysis.